2007
DOI: 10.5194/bg-4-195-2007
|View full text |Cite
|
Sign up to set email alerts
|

Manganese content records seasonal upwelling in Lake Tanganyika mussels

Abstract: Abstract. Biogenic productivity of Lake Tanganyika is highly dependent on seasonal upwellings of cold, oxygendepleted, nutrient-rich deep waters. We investigated the shell of freshwater bivalve Pleiodon spekii as a geochemical archive of these periodic hydrological changes tuned by the monsoon regime. The results of a three-year-long limnological and geochemical survey of the coastal waters performed on the dissolved and particulate fractions were compared to LA-ICP-MS profiles of Mn in five aragonitic shells … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 32 publications
0
26
0
2
Order By: Relevance
“…Very high values may be related to spikes in phytoplankton productivity and Mn oxy(hydr)oxide formation within the microenvironments produced by phytoplankton such as pelagic algal clumps (Richardson et al, 1988). This particular manganese may be further consumed by the bivalves (i.e., Langlet et al, 2007). For example, Nystrom et al (1996) observed Mn peaks in A C C E P T E D M A N U S C R I P T…”
Section: Accepted Manuscriptmentioning
confidence: 94%
“…Very high values may be related to spikes in phytoplankton productivity and Mn oxy(hydr)oxide formation within the microenvironments produced by phytoplankton such as pelagic algal clumps (Richardson et al, 1988). This particular manganese may be further consumed by the bivalves (i.e., Langlet et al, 2007). For example, Nystrom et al (1996) observed Mn peaks in A C C E P T E D M A N U S C R I P T…”
Section: Accepted Manuscriptmentioning
confidence: 94%
“…Some of the routinely recorded trace elements in shells are excellent markers or proxies of certain parameters of the studied waterways. Mn 2þ has been proposed as indicator of algal productivity (Vander Putten et al, 2000;Langlet et al, 2006Langlet et al, , 2007Caroll and Romanek, 2008;Siegele et al, 2001;Lazareth et al, 2003) and as such an ideal proxy of the rate of dissolved oxygen in the water (Mutvei and Westermark, 2001;Ravera et al, 2003Ravera et al, , 2007Caroll and Romanek, 2008). Fe 2þ , Zn 2þ are soluble in relation to the acidity of the medium and as such may record fluctuations in the pH (Stumm and Morgan, 1996;Mutvei and Westermark, 2001).…”
Section: Methodsmentioning
confidence: 97%
“…Frank and Gerstmann (2007) hypothesized that the decline in freshwater pearl mussels (Margaritifera margaritifera) throughout Europe is due to pollutants that affecting calcium metabolism, resulting in brittle shells. Langlet et al (2007) proposed using the shell of the freshwater bivalve, Pleiodon spekii, as a geochemical archive to assess seasonal changes of Lake Tanganyika, Africa. Ravera et al (2007) assessed the impact of lake trophy on trace element accumulation by comparing two different populations of freshwater mussels (Unio pictorum mancus).…”
Section: Regulatory Guidancementioning
confidence: 99%